1996
DOI: 10.1111/j.1476-5381.1996.tb16035.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the human brain putative A2B adenosine receptor expressed in Chinese hamster ovary (CHO.A2B4) cells

Abstract: 1 An [3H]-adenine pre-labelling methodology was employed to assay cyclic AMP generation by adenosine analogues in Chinese hamster ovary (CHO.A2B4) cells, transfected with cDNA which has been proposed to code for the human brain A2B adenosine receptor, and in guinea-pig cerebral cortical slices. 3 Of these agents, NECA was observed to exhibit the greatest intrinsic activity in CHO.A2B4 cells (ca. 10 fold stimulation of cyclic AMP), while, in comparison, maximal responses to adenosine (32% NECA response), 2-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
49
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 14 publications
8
49
0
Order By: Relevance
“…In the cord and chorionic vessels the receptors are mainly on smooth muscle, while in the cotyledon vessels P2Y 1 and P2Y 2 receptors were equally distributed between endothelial and smooth muscle cells. mRNA for P2Y 4 , P2Y 6 and P2Y 11 receptors was also found. P2X1, P2X4 and P2X7 receptors were also present on the smooth muscle of human chorionic blood vessels [408].…”
Section: Placentamentioning
confidence: 93%
See 3 more Smart Citations
“…In the cord and chorionic vessels the receptors are mainly on smooth muscle, while in the cotyledon vessels P2Y 1 and P2Y 2 receptors were equally distributed between endothelial and smooth muscle cells. mRNA for P2Y 4 , P2Y 6 and P2Y 11 receptors was also found. P2X1, P2X4 and P2X7 receptors were also present on the smooth muscle of human chorionic blood vessels [408].…”
Section: Placentamentioning
confidence: 93%
“…It was also shown that functional expression of human CFTR in the plasma membrane of CHO cells infected with adenovirus regulated the increase in intracellular Ca 2+ produced by ATP released from the cells. A 2B receptors have also been identified on CHO cells [6].…”
Section: Female Reproductive Organsmentioning
confidence: 97%
See 2 more Smart Citations
“…The inclusion of 300 M IBMX should block P1 receptor activation as this compound is a general low potency P1 antagonist (Fredholm et al, 1994). However, to eliminate this possibility we stimulated cells with 2-MeSADP in the additional presence of the nonselective P1 antagonist CGS 15943 (Alexander et al, 1996). This treatment had no significant effect on the ability of 2-MeSADP to inhibit glucagon-stimulated cyclic AMP levels.…”
Section: Activation Of Glycogen Phosphorylase By 2-mesadp In Freshly mentioning
confidence: 99%